Análisis comparativo para la implementación de una red de servicios convergentes (red nacional servientrega) - Armijos Saldaña, Evelyn Mercedes (2009)
Since in a short period of time, Voice over IP has become the daily transport of voice communications, new technologies have been developed to meet the standards required for its implementation. This is not only promising in terms of saving costs for domestic and international long distance calls and for the services that the integration provides; also by the management and operation costs reduction, using a single infrastructure network for voice and data services, as well as the diminution of the equipment used. The reach of this thesis project is the development of VoIP application in Servientrega’s company, which will use the data network already in place and operational. In the convergence process, communication servers of ALCATEL technology will be used for providing the connectivity to the traditional phone network and data network, this one will have quality of service and bandwidth upgrades capability. Warranting in this way calls reliability and data transmission performance.